Peran Ketahanan Organisasi dalam Pengaruh Kepemimpinan Transformasional dan Komitmen Organisasi terhadap Kinerja Organisasi pada Sektor Manufaktur - Liora Madya Elviranita Telaumbanua; Agustinus Setyawan; Alden Nelson (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Human resources are a vital asset for companies in achieving their goals, with transformational leadership and organizational commitment serving as key factors in acquiring high-quality human capital. This study aims to examine the role of organizational resilience in strengthening the influence of transformational leadership and organizational commitment on organizational performance in the manufacturing sector. In an increasingly dynamic business environment, organizational resilience becomes a crucial factor in maintaining optimal performance. Effective transformational leadership and strong organizational commitment are often identified as two main pillars in improving organizational performance. However, challenges from both external and internal environments demand organizations to possess resilience in order to adapt and survive. This study employs a quantitative approach by collecting data through a survey conducted in manufacturing companies in Batam. The analysis results indicate that organizational resilience serves as a significant mediating variable in the relationship between transformational leadership and organizational commitment on organizational performance. These findings highlight the importance of developing transformational leadership strategies that foster resilience, as well as enhancing organizational commitment to achieve sustainable performance.